2010
DOI: 10.1007/s11426-010-0182-0
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and distribution of 17 organochlorine pesticides (OCPs) in seawater from the Japan Sea northward to the Arctic Ocean

Abstract: Seventeen classic organochlorine pesticides in surface seawater were studied in terms of their composition pattern as well as their distribution pattern in the areas covering the Japan Sea, Okhotsk Sea, Bering Sea, Chukchi Sea and Arctic Ocean. Their concentrations varied, but roughly two levels were seen with one ranging between 0.1 and 1 ng L-1 for most HCH isomers and the other lower than 0.1 ng L-1 for other chemicals. Of the 17 target compounds, HCHs were dominant with a total concentration percentage gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
5
11
0
Order By: Relevance
“…The levels of α‐HCH generally increased with latitude in surface seawater, while the other six OCPs decreased with latitude increasing. The climbing levels of α‐HCH are consistent with other analyses from the same region (Cai et al, 2010, 2012). Compared to findings from previous studies, concentrations of α‐ HCH along the Bering Sea to the Arctic Ocean transect were much lower than that from sampling in 1988, 1993, and 1999 but higher than that from sampling in 2010 (Table S9).…”
Section: Resultssupporting
confidence: 90%
“…The levels of α‐HCH generally increased with latitude in surface seawater, while the other six OCPs decreased with latitude increasing. The climbing levels of α‐HCH are consistent with other analyses from the same region (Cai et al, 2010, 2012). Compared to findings from previous studies, concentrations of α‐ HCH along the Bering Sea to the Arctic Ocean transect were much lower than that from sampling in 1988, 1993, and 1999 but higher than that from sampling in 2010 (Table S9).…”
Section: Resultssupporting
confidence: 90%
“…Respect to concentrations values reported earlier for this area, γ-HCHs values reported by Cai et al (2010) showed a level comparable to that reported in 1999, but a slightly decreasing trend was observed for α-HCH. Water samples collected in the western Arctic Ocean presented concentrations of 2.07-2.63 ng/L and 0.33-070 ng/L for α-HCH and γ-HCH, respectively.…”
Section: Was Higher Than Values Fromsupporting
confidence: 81%
“…Surface seawater samples were collected during the third Chinese Arctic expedition cruise from July to September 2008 on board the R/V "Xuelong" The track covered the Japan sea, Okhotsk sea, Bering sea and the zone to the North of the Bering Strait including the Chukchi sea, Canadian Basin and Arctic ocean. Cai et al (2010) found that among the organochlorine pesticides, HCHs, especially α-HCH and γ-HCH, were the most predominant in the Arctic surface water body as found by other authors (Iwata et al, 1993;Chernyak et al, 1995;Jantunen et al, 1995;Yao et al, 2002;Weber et al, 2006). This trend might be attributable to the higher historic usage of HCHs compared to the other investigated compounds (Li and McDonald, 2005).…”
Section: Was Higher Than Values Frommentioning
confidence: 59%
See 1 more Smart Citation
“…The main reason of the pollution is the indiscriminate use of PCP for several decades [38]. Studies show that PCP residues are still measured at high level in several environmental matrices, such as soil, water, sediment, organic matter suspension, atmosphere, and even in many organisms [52][53]. Thus, the use of biological degradation techniques is very important because these methodologies promote the complete mineralization of this compound or conversion to harmless products [54].…”
Section: Pentachlorophenolmentioning
confidence: 99%